Mites of Greenhouses : - Zhang, Zhi-Qiang (CABI Publishing, 2003)
Mites are among the most important arthropods in greenhouses, both as pests causing economic injury to greenhouse crops, and as natural enemies used in the biological control of pest insects and other mites. Because of their minute size, mites are much less well known than insects.This book describes the biology, identification and control of such mites and the topics covered include an introduction to the Acari, illustrated keys to orders, families and selected species, the control of pest mites, and the role of beneficial mites in biological control. The book will be of interest to those working in entomology, crop protection and horticulture (editoral review)